HER2-targeted therapy combined with multidisciplinary management in advanced gallbladder cancer: a case report with 90-month survival - Wang, Yulin; Tian, Guangwei; Cheng, Yu; Wu, Shuang; Wei, Yanfang; Fan, Shize; Qu, Jinglei; Wang, Jin (Frontiers in Oncology, 2025)
Biliary tract malignancies are highly lethal, with a 5-year overall survival (OS) rate of less than 10%. This report describes a patient with HER2-positive advanced gallbladder cancer who achieved an OS of 90 months through multidisciplinary interventions and anti-HER2 targeted therapy. The patient achieved a prolonged period of disease stability, who was treated with various anti-HER2 targeted therapy, such as trastuzumab combined with pyrotinib and HER2-targeted antibody-drug conjugate (ADC). The patient received multiple local treatments (e.g., surgery, cryoablation, CyberKnife, and particle implantation) to further control the disease progression. Dynamic CA199 levels paralleled the treatment efficacy. This report underscores the significance of molecular profiling-guided personalized therapy and integrated multidisciplinary management in the treatment of biliary tract cancers.